STUDENT PERCEPTIONS OF CHATGPT FOR STATISTIC LEARNING: A TECHNOLOGY ACCEPTANCE MODEL (TAM) APPROACH: ANALISIS PERSEPSI MAHASISWA TERHADAP CHATGPT DALAM PEMBELAJARAN STATISTIKA: PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Siva Nur Samrotissaadah -; Kemas Muslim Lhaksmana (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Many students consider statistics one of the difficult subjects to learn throughout their academic period because of many complex theories and statistical analysis methodologies, which can increase anxiety in the learning process. Generative Artificial Intelligence gives birth to ChatGPT, which provides interesting descriptions and allows independent learning. Nevertheless, not enough literature is found regarding the use of ChatGPT in the context of statistics learning, particularly in Indonesia. In this study, we aim to analyze the perceptions of using ChatGPT as a tool in statistics education through Technology Acceptance Model (TAM). A survey with a quantitative approach was conducted with 203 statistics learners (103 females, 100 males) who have already used ChatGPT. To obtain the data, Likert scale questionnaire was used, and PLS-SEM was applied in analyzing data through five constructs of Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Using (AT), Behavioral Intention (BI), and Actual Use (AU). It was found that all five hypotheses were confirmed, and all relationships between constructs of TAM were positive and significant. Particularly, PEOU significantly affected PU (β = 0.347) and AT (β = 0.255), while AT had the highest impact on BI (β = 0.330). These findings indicate that ChatGPT is perceived as an assisting technological tool for learning statistics, where usability and attitudes of users become very crucial factors.